MECHANICAL PROPERTIES OF INCONEL 617B ALLOYAT ULTRA-SUPERCRITICAL TEMPERATURE - YIN Tao; CAI LiXun; BAO Chen (Jixie qiangdu)
A group of tests on uniaxial tension and low cyclic fatigue under constant strain amplitude at room temperature and 700 ℃ have been carried out for ultra-supercritical Inconel 617B alloy. Based on new method of finite-element-analysis aided testing on funnel specimen,we can get uniaxial tensile true stress-true strain curves until fracture. Then,fractured stress and strain,described equation of the true stress-true strain curves and parameters of the equation at two temperatures are obtained. At last,Evolutive behavior of cyclic stress,cyclic constitutive relationships,relationships between strain amplitudes and cyclic lives,ultra-supercritical temperature effects are studied. The results show that,ultra-supercritical temperature makes the elastic modulus of Inconel 617B,yield strength,ultimate strength,critical breaking stress,breaking strain and stress triaxiality of centre point on funnel root transversal surface after specimen necking decrease significantly. The curves obtained by FAT are well described by the new equation of the true stress-strain relationship. The finite-element-analysis shows that stress triaxiality of centre on funnel root transversal surface is the largest than other points,the maximum of fractured stress triaxiality at 700 ℃ is much lower than room temperature. 617B Inconel alloy performs obvious cyclic hardening characteristics at two temperatures. The cyclic stable life percent of 617B Inconel alloy reduces greatly and the anti-fatigue property weakens significantly under ultrasupercritical temperature. Manson-Coffin life-prediction model can describe the low cyclic fatigue life under two temperatures very well.